TNC Motives for Signing International Framework Agreements: A Continuous Bargaining Model of Stakeholder Pressure - Egels-Zandén, Niklas (Journal of business ethics, 2009)
Over the past decade, discussion has flourished among practitioners and academics regarding workers’ rights in developing countries. The lack of enforcement of national labour laws and the limited protection of workers’ rights in developing countries have led workers’ rights representatives to attempt to establish transnational industrial relations systems to complement existing national systems. In practice, these attempts have mainly been operationalised in unilateral codes of conduct; recently, however, negotiated international framework agreements (IFAs) have been proposed as an alternative. Despite their growing importance, few studies have empirically studied IFAs. This paper starts to fill this gap by studying why corporations adopt IFAs, based on a qualitative study of the process leading to the signing of a recent IFA. The study’s findings complement existing research into why corporations adopt IFAs, codes of conduct, and CSR policies by demonstrating that corporate motives can be linked to a desire to retain a trusting relationship with the labour union movement. In addition, the findings indicate that the discrete campaign model of stakeholder pressure dominant in previous research should be complemented by a continuous bargaining model of stakeholder pressure. The paper concludes by discussing differences between these conceptual models of stakeholder pressure and avenues for future research.